Oral feeding practices and discharge timing for moderately preterm infants. (May 2018) - Brumbaugh, Jane E.; Colaizy, Tarah T.; Saha, Shampa; Van Meurs, Krisa P.; Das, Abhik; Walsh, Michele C.; Bell, Edward F.; ,
Abstract: Background: Oral feeding skills of moderately preterm infants are not mature at birth. Aims: To establish the relationship between postmenstrual age at introduction of first oral feeding and attainment of full oral feeding and hospital discharge for moderately preterm infants. Study design: Multicenter retrospective analysis of a prospective cohort of moderately preterm infants admitted to a Eunice Kennedy Shriver National Institute of Child Health and Human Development Neonatal Research Network hospital. Subjects: 6146 infants born at 29–33 weeks' gestation from January 2012 to November 2013. Outcome measures: Postmenstrual age at full oral feeding and at hospital discharge. Results: The median postmenstrual age at first oral feeding was 33.9 weeks (interquartile range 33.1–34.3). For each week earlier at first oral feeding, full oral feeding occurred 4.5 days earlier (p < 0.0001) and hospital stay was shortened by 3.4 days (p < 0.0001). Higher birth weight (p < 0.0001) and black maternal race (p = 0.0001) were associated with younger postmenstrual age at full oral feeding and at discharge. Conclusion: Moderately preterm infants with earlier introduction of oral feeding achieved earlier full oral feeding and hospital discharge. Highlights: Age at introduction of oral feeding is associated with age at which full oral feeding and hospital discharge are attained. For each week earlier in postmenstrual age at first oral feeding, full oral feeding occurred 4.5 days sooner. For each week earlier in postmenstrual age at first oral feeding, postmenstrual age at discharge was 3.4 days younger. A prospective trial to evaluate whether earlier introduction of oral feeding facilitates earlier discharge is needed.